Blood and Cerebrospinal Fluid α‐Tocopherol and Selenium Concentrations in Neonatal Foals with Neuroaxonal Dystrophy. (22nd September 2015) - Finno, C.J.; Estell, K.E.; Katzman, S.; Winfield, L.; Rendahl, A.; Textor, J.; Bannasch, D.L.; Puschner, B.
Abstract : Background: Equine neuroaxonal dystrophy/equine degenerative myeloencephalopathy (NAD/EDM) is a neurodegenerative disorder affecting genetically predisposed foals maintained on α‐tocopherol (α‐TP)‐deficient diet. Objective: Intramuscular α‐TP and selenium (Se) administration at 4 days of age would have no significant effect on serum or cerebrospinal fluid (CSF) α‐TP in healthy foals. Serum and CSF α‐TP, but not Se, would be significantly decreased in NAD/EDM‐affected foals during first year of life. Animals: Fourteen Quarter horse foals; 10 healthy foals supplemented with 0.02 mL/kg injectable α‐TP and Se (n = 5) or saline (n = 5) at 4 days of age and 4 unsupplemented NAD/EDM‐affected foals. Methods: Complete neurologic examinations were performed, blood and CSF were collected before (4 days of age) and after supplementation at 10, 30, 60, 120, 180, 240, and 360 days of age. Additional blood collections occurred at 90, 150, 210, and 300 days. At 540 days, NAD/EDM‐affected foals and 1 unsupplemented healthy foal were euthanized and necropsies performed. Results: Significant decreases in blood, CSF α‐TP and Se found in the first year of life in all foals, with most significant changes in serum α‐TP from 4–150 days. Dam α‐TP and Se significantly influenced blood concentrations in foals. Injection of α‐TP and Se did not significantly increase CSF Se, blood or CSF α‐TP in healthy foals. NAD/EDM‐affected foals had significantly lower CSF α‐TP through 120 days. Conclusions and Clinical Importance: Injection of α‐TP and Se at 4 days of age does not significantly increase blood or CSF α‐TP. Despite all 14 foals remaining deficient in α‐TP, only the 4 genetically predisposed foals developed NAD/EDM.